Computationally bounded rationality from three perspectives: precomputation, regret tradeoffs, and lifelong learning - Orton, T (2023)
What does it mean for a computer program to be optimal? Many fields in optimal decision making, from game theory to Bayesian decision theory, define optimal solutions which can be computationally intractable to implement or find. This is problematic, because it means that sometimes these solutions are not physically realizable. To address this problem, bounded rationality studies what it means to behave optimally subject to constraints on processing time, memory and knowledge. This thesis contributes three new models for studying bounded rationality in different contexts.